Genetic Variation of the CYP2C9 Genetic of Minangkabau as a Predictor of Side Effect Providing Indications of Non-steroidal Anti-inflammatory Drugs - Katar, Yusticia; Usman, Elly; Aliska, Gestina (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Non-steroidal Anti-inflammatory Drugs (NSAID) activity showed a varied response based on the genetic polymorphism of the CYP29C enzyme. Metabolism of some NSAIDs such as celecoxib, diclofenac, and ibuprofen is highly dependent on CYP2C9. This enzyme has several variants of the heterozygous and homozygous genotypes such as CYP2C9 *2/2 and CYP2C9 *1/*3 which differ for each population. Genetic testing for specific variations of this allele will help determine whether the drug is a valid pharmacotherapeutic option for the patient or not. AIM: This study aims to analyze the genetic variation of the CYP2C9 gene from the Minangkabau ethnic, West Sumatra, Indonesia, which can later be used as a determinant of selecting the right NSAID with optimal effectiveness and to minimalize side effects. MATERIAL AND METHODS: Respondents of this study were users of NSAID drugs obtained from several hospitals in Padang City and were of Minang ethnicity. Blood samples taken from patients were stored in EDTA tubes and DNA was isolated using a genomic DNA isolation kit, DNAzol® Genomic DNA Kits (Thermofischer Scientific). PCR primer and sequencing were designed using Primer Blast (NCBI) software. The synthesized primer was purified by HPLC. DNA fragment application was carried out using the PCR method. The amplicon DNA was purified and prepared as much as 500 ng for sequencing using Illumina’s Next Generation Sequencing method. This analysis was performed with the help of SPSS software. RESULTS: When analyzing the CYP2C9 gene on Primer F23, 44 people were found to be homozygous for the normal allele (AA genotype), and 11 people were heterozygous (GT genotype), 45 people were normal allele (TT genotype), five people were heterozygous (CG genotype), 49 people were normal allele (AA genotype), and five people were heterozygous (GA genotype). CONCLUSION: This study concluded that relationship between CYP29C genetic variation and NSAID drug metabolism is found at the genotypic frequency rs229837 and rs1934969.